Prognostic value of the lymphocyte monocyte ratio in patients with colorectal cancer: A meta-analysis - Song, Wei (Medicine (Baltimore), 2016)
BACKGROUND: Inflammation plays a critical role in the pathogenesis and progression of cancer. A low lymphocyte-to-monocyte ratio (LMR) is reported be a poor prognostic factor in multiple malignancies. We performed a meta-analysis to evaluate the prognostic role of preoperative LMR in colorectal cancer (CRC). METHODS: Studies investigating the prognostic role of preoperative LMR on survival in patients with CRC were systematically searched for in MEDLINE, EMBASE, Cochrane databases from inception up to August 2016. Pooled hazard ratios (HRs) for overall survival (OS), disease-free survival (DFS), and recurrence-free survival (RFS) were calculated using fixed-effects/random-effects models. RESULTS: A total of nine studies comprising 8626 patients with CRC were included in the meta-analysis. The pooled analysis demonstrated that low LMR was significantly associated with decreased OS (HR: 0.63, 95% CI: 0.56–0.70, P < 0.001) and DFS/RFS (HR: 0.76, 95% CI: 0.68–0.84, P < 0.001). The negative prognostic impact of low LMR on OS was observed in patients with different ethnicity, treatment methods, cut-off values, and across disease stages. CONCLUSIONS: This meta-analysis demonstrates that low preoperative LMR is associated with worse survival in patients with CRC.